Creation, destruction, and transfer of atomic multipole moments by electron scattering: relativistic treatment 1 - Csanak, G.; Fontes, C.; Kilcrease, D.; Fursa, Dmitry (NRC Research Press, 2011)
We have obtained expressions for the creation, destruction, and transfer of atomic multipole moments by electron scattering under relativistic conditions. More specifically, we have obtained separate expressions for different-level processes (inelastic scattering) and for same-level processes (elastic and inelastic scattering). The cross sections for different-level processes are expressed in terms of inelastic magnetic sublevel cross sections, except for the coherence transfer cross section, which is expressed in terms of an angular integral of a product of inelastic magnetic sublevel amplitudes. The same-levelcross sections are expressed in terms of the imaginary part of the elastic forward scattering amplitude and in terms of elastic scattering magnetic sublevel cross sections, except for the coherence transfer cross section, which is expressed in terms of the (complex) forward elastic scattering amplitudes and an angular integral of a product of elastic scattering magnetic sublevel amplitudes. If the collisional model supports the optical theorem, then the same-level cross sections can be rewritten in such a form that they are broken up into two parts: an elastic scattering part and an inelastic scattering part. In carrying out this work, we have used the density matrix formalism of Fano and Blum in combination with the electron scattering formalism of Gell-Mann and Goldberger.